2009
DOI: 10.1021/jf901019y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Two Novel Low Phytic Acid (lpa) Soybean Mutants

Abstract: A GC-based approach was applied to compare the metabolite profiles of two low phytic acid (lpa) soybean mutants and their respective wild-types. The lpa mutants (Gm-lpa-TW75-1 and Gm-lpa-ZC-2) were grown together with the wild-types (Taiwan 75 and Zhechun no. 3) in three and four field trials, respectively. HPLC analysis revealed a phytic acid reduction of -53% for Gm-lpa-TW75-1 and of -46% for Gm-lpa-ZC-2. For Gm-lpa-TW75-1, no accumulation of lower inositol phosphates was observed, whereas Gm-lpa-ZC-2 exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 37 publications
8
54
0
1
Order By: Relevance
“…Additional research is needed to obtain low phytic acid phenotypes that result in field emergence comparable to normal phytic acid phenotypes. Soluble carbohydrates metabolite profiling of low phytic acid (lpa) mutant soybean seeds detected reduced myo-inositol, galactinol, raffinose, stachyose, galactopinitol A, galactopinitol B, and fagopyritol B1 compared to the wild type (Frank et al, 2009). These results are similar to those observed for LRSP1 and LRSP2 seeds expressing the mutant mips phenotype (Tables 1 & 2).…”
Section: Phytic Acidsupporting
confidence: 79%
See 1 more Smart Citation
“…Additional research is needed to obtain low phytic acid phenotypes that result in field emergence comparable to normal phytic acid phenotypes. Soluble carbohydrates metabolite profiling of low phytic acid (lpa) mutant soybean seeds detected reduced myo-inositol, galactinol, raffinose, stachyose, galactopinitol A, galactopinitol B, and fagopyritol B1 compared to the wild type (Frank et al, 2009). These results are similar to those observed for LRSP1 and LRSP2 seeds expressing the mutant mips phenotype (Tables 1 & 2).…”
Section: Phytic Acidsupporting
confidence: 79%
“…Kadlec et al (2001) itemize several plant sources from which standard cyclitols and galactosyl cyclitols may be isolated and provide detailed comparisons of commonly used methods of analysis. Some useful references for the preparation of cyclitols, galactopinitols, fagopyritols, and galactosyl myo-inositols include: Ford, 1985;Schweizer et al, 1978;Quemener & Brillouet, 1983;Schweizer & Horman, 1981;Nicolas et al, 1984;Gantner et al, 1991;Horbowicz & Obendorf, 1994;Horbowicz et al, 1998;Szczecinski et al, 1998Szczecinski et al, & 2000Obendorf et al, 2000;Steadman et al, 2001;Streeter, 2001;Frank et al, 2009 …”
Section: Analysis Of Soluble Carbohydratesmentioning
confidence: 99%
“…Long-lasting transgenerational plasticity can, however, not be fully excluded and we therefore refer further to (epi)genetic factors (Verhoeven et al 2016). Although (epi)genetic factors are generally considered less determining than environmental factors (Robinson et al 2007;Frank et al 2009;Matsuda et al 2012), our results demonstrate a clear (epi)-genetic signal of metabolic differentiation along T. urticae's invasion gradient. We acknowledge, however, that we cannot exclude neutral processes, such as, for example, serial bottlenecks -including surfing mutations (Klopfstein et al 2006;Travis et al 2007) as potential (co)sources of the found latitudinal metabolomic patterns.…”
Section: Discussionmentioning
confidence: 67%
“…The mutant Oslpa-XS110-1 showed a significant segregation from the associated wild type due to the polar metabolite profiles in this mutant. This was less evident for the other mutant/wild type comparison but the rice lines were well differentiated by growth location (Frank et al, 2009). More detailed analysis at the compound level of mutation-derived variation showed that these were largely accounted for by methyl pentadecanoate, galactose, raffinose, myoinositol and phosphate, the last two being key components in the phytic acid biosynthetic pathway (Frank et al, 2007) Fragrant rices (such as the well-known Jasmine and Basmati varieties) have also already been the subject of preliminary metabolomics analyses.…”
Section: Rice Metabolomicsmentioning
confidence: 85%